Science laboratory classroom environments in Korean high schools - Fraser, Barry; Lee, Sunny Seon Uk (Springer, 2009)
In order to investigate the learning environment of senior high school science laboratory classrooms in Korea, the Science Laboratory Environment Inventory (SLEI) was translated into Korean and administered to 439 students (99 science-independent stream students, 195 science-oriented stream students and 145 humanities stream students). Data analyses attested to the sound factorial validity and internal consistency reliability of the SLEI, as well as its ability to differentiate between the perceptions of students in different classrooms. Students in the science-independent stream generally perceived their science laboratory classroom environment more favourably than did students in either the humanities or science-oriented stream. Associations were found between various measures of students’ attitudes to science and their perceptions on SLEI scales; in particular, as in past research in other countries, integration between theory and practical classes was a statistically significant predictor of all attitude criteria when the other SLEI scales were mutually controlled.